Peace love yoga: the politics of global spirituality - Jain, Andrea R. (The master musicians, 2020)
Engaging with the growing popular and academic interest in the 'spiritual but not religious', Andrea R. Jain explores the connections between the practices of global spirituality and aspects of neoliberal capitalism in 'Peace Love Yoga'.